The Legal Regulation of Retirement Referral Disputes: A Comparative Study - Abdul Wahid Alawi, Lect .Dr. Ali (Basra studies journal, 2026)
Retirement referral disputes constitute a legal avenue available to retirees to challenge administrative authorities regarding decisions that place them into retirement. Such disputes restore the balance between the administration and its privileges on one hand, and the rights of retirees and the public interest on the other. This type of dispute is purely administrative, forming a category of retirement-related disputes that remains unchanged even if the authority to adjudicate is assigned to a body outside the administrative judiciary. Under Egyptian law, the adjudication of retirement referral disputes falls exclusively within the jurisdiction of the administrative judiciary, following their submission to examination committees established under the Social Insurance and Pensions Law. A similar arrangement applies in Iraq. However, these disputes are not submitted to preliminary committees as long as the employee’s functional relationship with the administration continues and the dispute is filed within the legally prescribed challenge period. If this period expires, the ordinary judiciary assumes jurisdiction, as it holds general authority over all disputes, including those involving the administration as a party. Nevertheless, such disputes fall outside the jurisdiction of the Retirees’ Case Audit Council, whose role is limited to appeals against decisions issued exclusively by the National Retirement Authority. Additionally, there is a legislative gap in the amended State Council Law No. 65 of 1979, as it does not provide effective mechanisms for disputes arising after the termination of the employment relationship. Despite the constructive role of the administrative judge, no initiative has been undertaken to address this legislative gap, and it has been affirmed that a retiree loses their legal standing once their employment relationship ends.